AN ANALYSIS FORM AND MEANING OF ONOMATOPOEIA IN “EGGNOID” DIGITAL COMIC - Zulaikah Zulaikah; Satria Andrianto; Reni Reni; Iis Juliana (PROJECT (Professional Journal of English Education), 2024)
This research describes the types of violations found in the film "Rudy Habibie" which uses Rudy as the main character. This pragmatic research approach uses descriptive methods. Data collection was carried out by watching films, writing down conversations so that a script could be made, then after collecting the data containing maxim violations into a table. Data analysis was carried out by grouping data based on type, strategy and function of maxim violation, analyzing and describing data results based on Grice's theory. The research results concluded that there were four types of maxim violations as follows: 23.27% violated the maxim of quantity, 58.62% violated the maxim of quality, 13.8% violated the maxim of relevance, and 4.31% violated the maxim of manner. Of the 116 data on maxim violations contained in films, maxim violations are violations committed by the main character with a percentage of 58.62% out of 100%.